EULAR recommendations for the management of familial Mediterranean fever. Issue 4 (22nd January 2016) - Ozen, Seza; Demirkaya, Erkan; Erer, Burak; Livneh, Avi; Ben-Chetrit, Eldad; Giancane, Gabriella; Ozdogan, Huri; Abu, Illana; Gattorno, Marco; Hawkins, Philip N; Yuce, Sezin; Kallinich, Tilmann; et al.
Abstract : Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease, but many rheumatologists are not well acquainted with its management. The objective of this report is to produce evidence-based recommendations to guide rheumatologists and other health professionals in the treatment and follow-up of patients with FMF. A multidisciplinary panel, including rheumatologists, internists, paediatricians, a nurse, a methodologist and a patient representative, was assembled. Panellists came from the Eastern Mediterranean area, Europe and North America. A preliminary systematic literature search on the pharmacological treatment of FMF was performed following which the expert group convened to define aims, scope and users of the guidelines and established the need for additional reviews on controversial topics. In a second meeting, recommendations were discussed and refined in light of available evidence. Finally, agreement with the recommendations was obtained from a larger group of experts through a Delphi survey. The level of evidence (LoE) and grade of recommendation (GR) were then incorporated. The final document comprises 18 recommendations, each presented with its degree of agreement (0–10), LoE, GR and rationale. The degree of agreement was greater than 7/10 in all instances. The more controversial statements were those related to follow-up and dose change, for which supporting evidence is limited. A set of widely accepted recommendations for the treatment and monitoring of FMF is presented, supported by the best available evidence and expert opinion. It is believed that these recommendations will be useful in guiding physicians in the care of patients with FMF.